Rancang Bangun Aplikasi Stock Opname Berbasis Java - Sandy, Agung Ferdinan; Anshary, Nico Bustanul; Lukman, Lukman (Universitas Indraprasta PGRI Jakarta, 2025)
Stock-taking is an important process in stock management to ensure a match between the mechanism data and the physical amount in the warehouse, but many companies still use manual methods that are prone to errors and inefficiencies. This research aims to create and build a Java-based stock-taking program to improve the accuracy and efficiency of stock data collection. The methods used include mechanism requirements analysis, design with Entity-Relationship Diagram (ERD) and Unified Modeling Language (UML), and implication using Java and MySQL database, with testing through Black Box Testing method. The results show that this program is able to assist users in recording, managing, and verifying stock more accurately and efficiently than manual methods, with key features such as automatic recording, fast stock search, and real-time report generation that support the effectiveness of the stock-taking process in the company.